2010
DOI: 10.1007/s11144-010-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of humic acids through heterogeneous catalytic ozonation with bone charcoal

Abstract: Catalytic ozonation has recently been used as a new means of contaminant removal from water and wastewater. In this study, bone charcoal (BC), a new catalyst prepared under laboratory conditions, was used to catalyze the ozonation of humic substances (HS) in aqueous solutions. The catalytic effect of bone charcoal and the relevant parameters of this ozonation process (solution pH, temperature, scavenger effect, humic acids concentration and BC dosage) were investigated. In the catalytic ozonation experiments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…It can be observed that the addition of AC and CeO 2 /AC catalysts improves the degradation efficiency of FA. The enhanced degradation efficiency of FA must be mainly attributed to an increase in the ozone decomposition into · OH radicals . In contrast, the adsorption by AC and 5%‐Ce(III)/AC‐H 2 ‐450 only contributed to 3.6% and 4.1% removal of FA after 30 min.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It can be observed that the addition of AC and CeO 2 /AC catalysts improves the degradation efficiency of FA. The enhanced degradation efficiency of FA must be mainly attributed to an increase in the ozone decomposition into · OH radicals . In contrast, the adsorption by AC and 5%‐Ce(III)/AC‐H 2 ‐450 only contributed to 3.6% and 4.1% removal of FA after 30 min.…”
Section: Resultsmentioning
confidence: 96%
“…In the presence of Fe/MgO catalyst, ozonation of humic acids induced a significant reduction in UV absorbance compared with ozonation alone . Addition of perfluorooctylalumina or bone charcoal in an ozonation process greatly accelerated the rate of HA degradation . Accordingly, catalysts can significantly improve the removal efficiency of HA from water in the ozonation process.…”
Section: Introductionmentioning
confidence: 99%
“…Mjengera and Mkongo [32] reported that BC prepared in 400°C could be used to remove fluoride from water. This sorbent can also be used as a catalyst in ozonation systems for humic acid removal from water [33].…”
Section: Adsorbent Characteristicsmentioning
confidence: 99%
“…The negative effect of a free radical scavenger t-BuOH suggested that the • OH radicals were involved in catalytic ozonation of HA (Chiang et al 2006;Mortazavi et al 2010).…”
Section: Mechanism Of Catalytic Ozonation Of Hamentioning
confidence: 99%
“…And the contributions of direct oxidation by ozone molecules and indirect oxidation by hydroxyl radicals depended on the solution pH (Chiang et al 2006). Moreover, the addition of solid catalysts such as Fe/MgO, perfluorooctylalumina and bone charcoal promoted the decomposition of ozone into • OH radicals and, therefore, greatly accelerated the rate of HA degradation compared to sole ozonation (Lee et al 2005;Ma and Chang 2010;Mortazavi et al 2010).…”
Section: Introductionmentioning
confidence: 99%